MASTER COURSES IN INTERNATIONAL LAW AT TECHNICAL UNIVERSITIES - Aleksandr S. Eremenko (Высшее образование в России)
The article deals with the certain social and economic issues of organization of international law master courses at higher schools of engineering and technologies. In modern conditions competency in international law becomes an indispensable element of professional skills of a specialist especially of managerial staff therefore master courses in law should be revised taking into account this aspect.